Mutation of the Polyproline Sequence in CD3ε Evidences TCR Signaling Requirements for Differentiation and Function of Pro-Inflammatory Tγδ17 Cells - Borroto, Aldo; Alarcón, Balbino; Navarro, María N. (Frontiers in Immunology, 2022)
Tγδ17 cells have emerged as a key population in the development of inflammatory and autoimmune conditions such as psoriasis. Thus, the therapeutic intervention of Tγδ17 cells can exert protective effects in this type of pathologies. Tγδ cells commit to IL-17 production during thymus development, and upon immune challenge, additional extrathymic signals induce the differentiation of uncommitted Tγδ cells into Tγδ17 effector cells. Despite the interest in Tγδ17 cells during the past 20 years, the role of TCR signaling in the generation and function of Tγδ17 cells has not been completely elucidated. While some studies point to the notion that Tγδ17 differentiation requires weak or no TCR signaling, other works suggest that Tγδ17 require the participation of specific kinases and adaptor molecules downstream of the TCR. Here we have examined the differentiation and pathogenic function of Tγδ17 cells in “knockin” mice bearing conservative mutations in the CD3ε polyproline rich sequence (KI-PRS) with attenuated TCR signaling due to lack of binding of the essential adaptor Nck. KI-PRS mice presented decreased frequency and numbers of Tγδ17 cells in adult thymus and lymph nodes. In the Imiquimod model of skin inflammation, KI-PRS presented attenuated skin inflammation parameters compared to wild-type littermates. Moreover, the generation, expansion and effector function Tγδ17 cells were impaired in KI-PRS mice upon Imiquimod challenge. Thus, we conclude that an intact CD3ε-PRS sequence is required for optimal differentiation and pathogenic function of Tγδ17 cells. These data open new opportunities for therapeutic targeting of specific TCR downstream effectors for treatment of Tγδ17-mediated diseases.